2023
DOI: 10.1007/s10055-023-00768-1
|View full text |Cite
|
Sign up to set email alerts
|

Immersive virtual reality for improving cognitive deficits in children with ADHD: a systematic review and meta-analysis

Abstract: Virtual reality (VR) shows great potential in treating and managing various mental health conditions. This includes using VR for training or rehabilitation purposes. For example, VR is being used to improve cognitive functioning (e.g. attention) among children with attention/deficit-hyperactivity disorder (ADHD). The aim of the current review and meta-analysis is to evaluate the effectiveness of immersive VR-based interventions for improving cognitive deficits in children with ADHD, to investigate potential mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 81 publications
0
12
0
1
Order By: Relevance
“…Nevertheless, most of the mentioned reports in systematic reviews do not mention monitoring complications of this technology, as if it comes with pure benefit. [6,7,12,13] In this study, we identified a total of 4 controlled trials on skill development in autism, ADHD, and dyslexia; comprising a total of 208 patients, a sample size that does not match a very large population of interest. [8][9][10][11] Moreover, the age ranged in the four studies from 6-16 years, which means that VR technology is still not extensively available for early training of patients with learning difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most of the mentioned reports in systematic reviews do not mention monitoring complications of this technology, as if it comes with pure benefit. [6,7,12,13] In this study, we identified a total of 4 controlled trials on skill development in autism, ADHD, and dyslexia; comprising a total of 208 patients, a sample size that does not match a very large population of interest. [8][9][10][11] Moreover, the age ranged in the four studies from 6-16 years, which means that VR technology is still not extensively available for early training of patients with learning difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with severe phobias, a systematic review found VR exposure therapy to be just as effective as in vivo therapies, particularly for cases of acrophobia (the fear of heights), claustrophobia, and blood injection phobia (the fear of injection exposure), with significant reductions in levels of fear, anxiety, and avoidance [ 54 ]. Other successful use cases with meta-analytic evidence include VR in palliative care [ 55 ], physical therapy and rehabilitation [ 56 ], and cognitive functioning (eg, memory and attention) [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some scholars have attempted to use game interventions to assist in the treatment of ADHD patients, with VR being one of the new intervention methods [18]. VR technology, also known as 'spiritual realm' technology, is a comprehensive information technology that integrates computer graphics, digital image processing, multimedia technology, computer simulation technology, sensor technology, display technology, and network parallel processing technology [19].…”
Section: Introductionmentioning
confidence: 99%